2014
DOI: 10.1200/jco.2014.56.5853
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Extended Schedule or Re-Treatment Trial for Low–Tumor Burden Follicular Lymphoma: Eastern Cooperative Oncology Group Protocol E4402

Abstract: Purpose In low–tumor burden follicular lymphoma (FL), maintenance rituximab (MR) has been shown to improve progression-free survival when compared with observation. It is not known whether MR provides superior long-term disease control compared with re-treatment rituximab (RR) administered on an as-needed basis. E4402 (RESORT) was a randomized clinical trial designed to compare MR against RR. Patients and Methods Eligible patients with previously untreated low–tumor burden FL received four doses of rituximab, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 20 publications
3
127
0
6
Order By: Relevance
“…The efficacy of this regimen in nodal FL was demonstrated in the RESORT trial. In low tumor burden nodal FL, a re-treatment strategy with rituximab 375 mg/m 2 for 4 weekly doses upon relapse provides disease control comparable to a rituximab maintenance strategy (23). The present case demonstrated the potential benefit of this protocol in GI-FL during initial treatment and nodal relapse.…”
Section: Discussionmentioning
confidence: 62%
“…The efficacy of this regimen in nodal FL was demonstrated in the RESORT trial. In low tumor burden nodal FL, a re-treatment strategy with rituximab 375 mg/m 2 for 4 weekly doses upon relapse provides disease control comparable to a rituximab maintenance strategy (23). The present case demonstrated the potential benefit of this protocol in GI-FL during initial treatment and nodal relapse.…”
Section: Discussionmentioning
confidence: 62%
“…5 Also, at least two randomized studies have shown that the time to the next nonrituximab treatment is the same, whether rituximab is administered continually as maintenance or intermittently, at every progression. 11,13 The second strategy is probably more cost effective because it uses less than one half of the rituximab without apparently compromising survival.…”
Section: Discussionmentioning
confidence: 99%
“…54 After induction therapy with single-agent rituximab, patients with low-tumor-burden FL were randomized to receive maintenance rituximab until treatment failure or to be periodically re-treated with rituximab (re-treated with 4 weekly doses at each progression) until treatment failure. The trial revealed no difference in the time to treatment failure between the 2 dosing strategies.…”
Section: Management Of Asymptomatic Low-tumor-burden Follicular Lympmentioning
confidence: 99%